Analysis of productions on the training of science teachers in the final years of elementary school and the teaching of astronomy (Research, Society and Development, 2022)
This work aims to investigate how the training of Science teachers in the final years of Elementary School, referring to the teaching of Astronomy, has been addressed in academic productions from 2010 to 2020. The research has a qualitative approach of the descriptive type, the data were constituted through a search in the Digital Library of Theses and Dissertations (BDTD) from the keywords “teaching of astronomy”; “Science teacher training” and “elementary education”. At the end, 10 dissertations that met the inclusion and exclusion criteria defined a priori were analyzed. Data analysis was performed based on the theoretical assumptions of Bardin's Categorical Content Analysis. From the research carried out, it was possible to show that the proposed approach has still been little questioned in academic productions. In this sense, we understand that we must (re)think the Education of Science Teachers, both initial and continuous, in order to contribute to overcoming obstacles to the teaching of Astronomy, as well as serving as a contribution so that, theoretically, methodologically or reflexively, the teacher has subsidies to properly conduct the teaching and learning process.